Mapping the Intellectual Structure of Impairment Testing in Financial Reporting Research: A Bibliometric Study - Judijanto, Loso; Setiyawan, Heri (The Es Accounting And Finance, 2026)
This study aims to map the intellectual structure and development of impairment research in financial reporting through a bibliometric approach. Using data extracted from the Scopus database covering the period 2000–2025, the analysis employs VOSviewer to examine co-occurrence of keywords, thematic clusters, and research evolution. The findings reveal that the literature is structured around several dominant themes, including cognitive impairment, visual impairment, and genetic perspectives, which are interconnected through methodological approaches such as cohort and longitudinal studies. The temporal analysis indicates a shift from early research focusing on diagnostic and measurement frameworks toward more recent studies emphasizing early detection, personalized approaches, and life-course perspectives. Furthermore, the results highlight the increasing integration of multidisciplinary insights, reflecting the complexity of impairment-related phenomena. This study contributes to the literature by providing a comprehensive overview of the field’s intellectual landscape, identifying key research trends, and offering directions for future research. The findings also offer practical implications for researchers and practitioners by emphasizing the importance of integrative and evidence-based approaches in understanding and managing impairment.